2017
DOI: 10.1007/s00221-017-5039-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of imagery capacity in motor performance improvement

Abstract: Motor imagery (MI) training improves motor performance, but the inter-individual variability of this improvement remains still unexplored. In this study, we tested the influence of imagery ability on the performance improvement following MI training. Twenty participants were randomly distributed into the MI or control group. They actually performed, at pre- and post-test sessions, a revisited version of the Nine Hole Peg Test, a speed-accuracy trade-off task, commonly used in clinics. Between the tests, the MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Motor task test: After this initial screening, 64 students remained who were randomly divided into 8 groups. In regard to the individual imagery abilities, subjects also filled out a recent revised version of the Vividness of Movement Imagery Questionnaire (VMIQ-2) to determine (on a 5point scale) the clarity with which they were able to imagine movements and especially the difference between their capacity to use internal and external visual imagery (44). Participants were divided homogeneously into one of these eight groups according to their score in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Motor task test: After this initial screening, 64 students remained who were randomly divided into 8 groups. In regard to the individual imagery abilities, subjects also filled out a recent revised version of the Vividness of Movement Imagery Questionnaire (VMIQ-2) to determine (on a 5point scale) the clarity with which they were able to imagine movements and especially the difference between their capacity to use internal and external visual imagery (44). Participants were divided homogeneously into one of these eight groups according to their score in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, in the field of rehabilitation, motor imagery training has shown to be beneficial in the recovery of an affected upper limb and balance in some systematic reviews (García Carrasco and Aboitiz Cantalapiedra, 2016;Guerra et al, 2017). Moreover, a previous study in healthy subjects has found high vividness scores to be related to greater improvement (Ruffino et al, 2017). These findings suggest that it is important how vividly a subject can perform motor imagery in order to practice effective motor imagery training.…”
Section: Clinical Implicationmentioning
confidence: 98%
“…In these studies, as supplementary data for accuracy of results, it is considered important to show the subject’s MI ability to form and control accurate mental images of movement and the quality and vividness of their image of the motor act (Guillot and Collet, 2005 ; Sharma et al, 2006 ). In particular, the Movement Imagery Questionnaire (MIQ; Malouin et al, 2007 ), Vividness of MIQ (VMIQ; Isaac et al, 1986 ), and Kinesthetic and Visual Imagery Questionnaire (KVIQ; Malouin et al, 2007 ) are used to measure the subject’s MI ability, whereas the visual analogue scale (VAS; Mateo et al, 2018 ) and Likert scale (Ruffino et al, 2017 ) describe the subjective perception of how clear and vivid the MI was. In the present study, we defined “MI ability assessment” as that which evaluates the subject’s MI ability with a task that is different from the task to be learned in MI training.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neuroimaging data have demonstrated that the imagined and actual movements are functionally equivalent in the sense they share the same neural circuitry [ 13 15 ]. It could be hypothesized that such neural circuitry might underlie the improvements in movement efficiency induced by MI, allowing athletes to improve the level of performance [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%